Board of Director Diversity in “Bhinneka Tunggal Ika” Concept - Nor Rahma Rizka; Rika Meidiana Rahayu; Yacobus Soegiarto (ITB AAS INDONESIA, 2022)
One of the mechanisms to implement good corporate governance is board of directors diversity. Studies found the board of directors diversity has a positive effect on firm performance. Bhinneka Tunggal Ika philosophy is the best symbol of unity in diversity of Indonesian. This study reflects the concept of